Immunogenicity of three doses of anti-SARS-CoV-2 BNT162b2 vaccine in psoriasis patients treated with biologics - Graceffa, Dario; Sperati, Francesca; Bonifati, Claudio; Spoletini, Gabriele; Lora, Viviana; Pimpinelli, Fulvia; Pontone, Martina; Pellini, Raul; Di Bella, Ornella; Morrone, Aldo; Cristaudo, Antonio (Frontiers in Medicine, 2022)
Introduction Psoriasis has not been directly linked to a poor prognosis for COVID-19, yet immunomodulatory agents used for its management may lead to increased vulnerability to the dangerous complications of SARS-CoV-2 infection, as well as impair the effectiveness of the recently introduced vaccines. The three-dose antibody response trend and the safety of BNT162b2 mRNA vaccine in psoriasis patients treated with biologic drugs have remained under-researched. Materials and Methods Forty-five psoriatic patients on biologic treatment were enrolled to evaluate their humoral response to three doses of BNT162b2. IgG titers anti-SARS-CoV-2 spike protein were evaluated at baseline (day 0, first dose), after 3 weeks (second dose), four weeks post-second dose, at the time of the third dose administration and four weeks post-third dose. Seropositivity was defined as IgG ≥15 antibody-binding units (BAU)/mL. Data on vaccine safety were also collected by interview at each visit. Results A statistically significant increase in antibody titers was observed after each dose of vaccine compared with baseline, with no significant differences between patients and controls. Methotrexate used in combination with biologics has been shown to negatively influence the antibody response to the vaccine. On the contrary, increasing body mass index (BMI) positively influenced the antibody response. No adverse effects were reported, and no relapses of psoriasis were observed in the weeks following vaccine administration in our study population. Conclusions Our data are largely consistent with the recent literature on this topic confirming the substantial efficacy and safety of BNT162b2 mRNA vaccine on psoriatic patients treated with biologics of different types and support the recommendation to perform additional doses in this specific subgroup of patients.